Zeitschrift für Slawistik (De Gruyter (A), 1956)
Zeitschrift für Slawistik publishes critical essays on languages and literatures, popular poetry, and the cultural history of Slavic peoples in the past and present. Special attention is paid to German-Slavic linguistics, literary and cultural relations within their European context, onomastics, history and poetology of literary genres, Baltic studies, Sorbian studies, and the history of Slavic studies.